Effectiveness of intramedullary nails in Tibiotalocalcaneal arthrodesis for Charcot neuroarthropathy: a systematic review and meta-analysis - Hao Zhang; Ning Jiang; Jun-Fei Zhao; Xian-Tie Zeng (Journal of Orthopaedic Surgery and Research)
Abstract Objective To systematically evaluate the efficacy and safety of intramedullary nails (IMNs) in tibial-talocalcaneal arthrodesis (TTCA) for treating Charcot neuroarthropathy (CN). Methods A comprehensive search for relevant literature was conducted in the PubMed, Embase, Cochrane Library, Web of Science, Scopus and SinoMed databases, covering studies from 2014 to October 30, 2024. The inclusion criteria were based on the PICOS framework: the study population consisted of CN patients, the intervention was TTCA with IMNs, and the outcomes assessed included bone union rate, complication rate, and limb salvage rate. Statistical analysis was performed using Stata 17.0 software. Literature quality was assessed using the Newcastle–Ottawa Scale (NOS) for cohort studies and case series. This systematic review was prospectively registered with the International Prospective Register of Systematic Reviews (PROSPERO; registration number: CRD42025644983). Results A total of seven studies involving 147 patients with a mean follow-up of one year were included. The meta-analysis revealed a combined standardized mean difference (SMD) of -4.99 (95% CI: -6.70 to -3.28) for the AOFAS score, with high heterogeneity (I2 = 90.7%). Sensitivity analyses were conducted to assess the stability of the results. The combined estimate for the bone nonunion rate was 3.3% (95% CI: 0.1% to 8.9%), with moderate heterogeneity (I2 = 33.2%). The combined estimate for the infection rate was 12.9% (95% CI: 2.0% to 29.2%). A comparison of preoperative and postoperative scores showed significant improvements in patients' function and quality of life, highlighting the critical role of the TTCA procedure in improving prognosis. Conclusion IMNs in TTCA demonstrate high efficacy for CN, with significant functional improvement, low nonunion rates, and favorable limb salvage outcomes. However, infection risks and heterogeneity across studies highlight the need for standardized protocols and larger controlled trials to optimize patient selection and postoperative management.